The development of the informal small-enterprise sector in Eastern and Southern Africa: From import substitution to structural adjustment - Poul Ove Pedersen (Danish Institute for International Studies (DIIS), 2005)
In spite of its growing importance in the African economies, the informal, small-enterprise sector still plays a dubious and little understood role in development. Due to lack of data it is often treated as if it was unrelated to the rest of the economy. However, a number og large surveys carried out in a number of African countries indicate that structure and development of the small-enterprise sector vary greatly both from country to country and over time, depending in a complex way on the national differences in socio-economic structures and policies. In order to understand the relationships between the small-enterprise sector and the rest of the economy we shall here investigate how the development of the small-enterprise sector has been changing in different countries in Eastern and Southern Africa first under the import-substitution era and then under the structural adjustment period. In the conclusion we present four theories of small-enterprise development often discussed in the literature and compare them to the development patterns found in the detailed analysis.
Keywords: 330; KMU; Informeller Sektor; Importsubstitution; Strukturwandel; Ostafrika; Südafrika